LEGAL PROTECTION FOR KOI FISH AUCTIONS ON WHATSAPP GROUPS AGAINST BID AND RUN - Putra, Bogananta Pratama; Santoso, Imam; Kurnia, Tata (FOCUS: Jurnal of Law, 2025)
This study examines the legal protection for koi fish auction operators conducting transactions through WhatsApp Groups who are harmed by the “bid and run” practice, where auction winners fail to fulfill payment obligations. The research aims to analyze the adequacy of existing legal frameworks in protecting business operators in informal digital auction transactions. Using a normative juridical method supported by limited empirical insights from interviews with auction operators, this study finds that legal protection remains weak due to the absence of written agreements, lack of specific regulation on online auctions, and evidentiary difficulties in WhatsApp-based transactions. The study concludes that the Civil Code and the ITE Law have not been optimally implemented in this context. It recommends the use of electronic agreements and clearer regulatory recognition of non-platform digital auctions to strengthen legal certainty for business operators.